From “Hartz IV” to “Bürgergeld” — Merely Old Wine in New Bottles? - Maximilian Blömer; Clemens Fuest; Andreas Peichl (Wirtschaftsdienst)
Abstract In this article, we discuss reform elements of “Hartz IV”. This includes, on the one hand, merging unemployment benefits with housing benefits and the additional child benefits (Kinderzuschlag) and, on the other hand, reducing disincentives which prevent the recipients from earning higher incomes. Employment incentives can be improved if the effective marginal transfer withdrawal rate is reduced and, at the same time, the preferential treatment of “mini jobs” is reduced. In addition, the eligibility criteria should be simplified. This could reduce the rate of non-takeup and thus hidden poverty. One criticism of such a reform of Hartz IV is that it would increase the number of transfer recipients. However, this is not an economically sensible outcome in a reform effort. What is important is the disposable income of transfer recipients affected and that the design of the transfer withdrawal does not create lock-in effects.